France : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
U.S. shocks explain a large part of French output common components. This paper analyzes the economic implications of two alternative welfare financing reforms: a reduction in payroll taxes funded by an increase in consumption taxes, and the other funded by a new levy on business value added. The importance of financial market constraints and whether the recent mortgage market reform is likely to ease these constraints is assessed. Rechargeable mortgages are attractive and encourage collateralization, but bolder measures are needed to limit legal and other fees.